Aplikasi Jasa Wedding Organizer Berbasis Web Di Kota Pagar Alam - Siti Muntari; Risnaini Masdalipa (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
Wedding Organizer is a service that provides special services to the bride and groom in the planning to the implementation of a series of wedding parties according to the schedule and budget that has been set by offering a variety of wedding concepts. The current system is still manual because visitors must come directly to the salon to see or order marital problems. The proposed system is making a web-based wedding organizer service application. There will be seven research sites, namely Borry salon, Damori salon, Borryz salon, Dwi Anggon wo, Dian bridal, Rizki jhava,Minhar salon, and Darmawansyah salon. Data collection methods used are observation, interviews, and literature study. The system development method uses the waterfall method with stages of analysis, design, coding, and testing. This system was developed using Adobe Dreamweaver, PHP, Mysql, and Xampp applications. Preliminary results for now in the form of a web-based wedding organizer services in the city of Pagar alam.